The Role of Financial Influencers on Social Media in Shaping People's Financial Literacy - Pipit Sari; Handriyani Dwilita (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2024)
Financial literacy is important aspect in life that can be improved to having better financial condition. Influencers at social media is people that can make their followers want to follow things that they shared at media social account. Finance influencer is influencer who often discuss about how to manage, organize, and plan finances well so that very useful at life now or in the future. This study is aimed at knowing the role of finance influencer at social media in forming public's financial literacy. This study uses qualitative descriptive technique. Data collected technique was using documentations and data analysis technique used was descriptive. The results of this study show that finance influencer have a role in forming public's financial literacy, one of the roles is giving the financial education at social media with interesting video and posts.